2019
DOI: 10.1165/rcmb.2017-0353oc
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Inositol Polyphosphate 4-Phosphatase Protects against Airway Inflammation and Remodeling

Abstract: The asthma candidate gene inositol polyphosphate 4-phosphatase type I A (INPP4A) is a lipid phosphatase that negatively regulates the PI3K/Akt pathway. Destabilizing genetic variants of INPP4A increase the risk of asthma, and lung-specific INPP4A knockdown induces asthma-like features. INPP4A is known to localize intracellularly, and its extracellular presence has not been reported yet. Here we show for the first time that INPP4A is secreted by airway epithelial cells and that extracellular INPP4A critically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Furthermore, it was shown in asthma that airway epithelial cells secrete the lipid phosphatase inositol polyphosphate 4-phosphatase type I A (INPP4A) in the form of extracellular vesicles, which negatively regulate the phosphatidylinositol 3-kinase/serine/threonine protein kinase B (PI3K/Akt) pathway and inhibit airway inflammation and remodeling. Antibody-mediated neutralization of this vesicular INPP4A induced airway hyperresponsiveness, with prominent airway remodeling, subepithelial fibroblast proliferation, and collagen deposition in a murine model of asthma [ 89 ]. The anti-inflammatory effects of BALF-EVs are listed in Table 2 .…”
Section: Balf-evs Modulate Inflammation In Pulmonary Diseasesmentioning
confidence: 99%
“…Furthermore, it was shown in asthma that airway epithelial cells secrete the lipid phosphatase inositol polyphosphate 4-phosphatase type I A (INPP4A) in the form of extracellular vesicles, which negatively regulate the phosphatidylinositol 3-kinase/serine/threonine protein kinase B (PI3K/Akt) pathway and inhibit airway inflammation and remodeling. Antibody-mediated neutralization of this vesicular INPP4A induced airway hyperresponsiveness, with prominent airway remodeling, subepithelial fibroblast proliferation, and collagen deposition in a murine model of asthma [ 89 ]. The anti-inflammatory effects of BALF-EVs are listed in Table 2 .…”
Section: Balf-evs Modulate Inflammation In Pulmonary Diseasesmentioning
confidence: 99%
“…In vitro experiments using cell lines demonstrated that AECs were able to secrete enzymatically active inositol polyphosphate 4-phosphatase type I A (INPP4A) in EVs and as a soluble free form. INPP4A was then transferred to lung fibroblasts, and inhibition of such transfer resulted in increased fibroblast proliferation [ 65 ]. Moreover, in mice with or without AAI neutralization of extracellular INPP4A-induced AHR, with prominent airway remodeling, subepithelial fibroblast proliferation, and collagen deposition [ 65 ].…”
Section: Extracellular Vesicles and Asthma: Cellular Levelmentioning
confidence: 99%
“…INPP4A was then transferred to lung fibroblasts, and inhibition of such transfer resulted in increased fibroblast proliferation [ 65 ]. Moreover, in mice with or without AAI neutralization of extracellular INPP4A-induced AHR, with prominent airway remodeling, subepithelial fibroblast proliferation, and collagen deposition [ 65 ]. EV-mediated interactions between major cellular players involved in asthma/AAI (reported in Section 5.1 , Section 5.2 , Section 5.3 , Section 5.4 and Section 5.5 ) are summarized in Figure 3 .…”
Section: Extracellular Vesicles and Asthma: Cellular Levelmentioning
confidence: 99%
“…Specifically, it has been shown that fibroblasts-derived EVs secreted by cells obtained from severe asthmatics increase proliferation of bronchial epithelial cells (HBECs) in comparison to those in healthy individuals, due to a decrease in the TGF-b2 content (178). Vice versa, vesicular transfer between epithelial cells and fibroblasts which includes inositol polyphosphate 4-phosphatase type I A (INPP4A) cargo, may regulate inflammation and airway remodeling (179). Further to that, Gupta et al have shown that sEV transfer between airway epithelial cells (AECs) and human tracheobronchial cells (HTBEs) promotes expression several proteins which may contribute to allergic inflammation and exacerbation of asthma symptoms, i.e.…”
Section: Asthmamentioning
confidence: 99%